STRICT S-NUMBERS OF THE VOLTERRA OPERATOR - Baksi, Ozlem; Khan, Taqseer; Lang, Jan; Musil, Vit (AMER MATHEMATICAL SOC, 2018)
For Volterra operator V : L-1(0, 1) -> C[0, 1] and summation operators : sigma l(1) -> c, we obtain exact values of Approximation, Gelfand, Kolmogorov and Isomorphism numbers.
Keywords: Integral operator; summation operator; s-numbers; HARDY-TYPE OPERATORS; WIDTHS; Mathematics